Modulation of endothelial and smooth muscle function by bed rest and hypoenergetic, low-fat nutrition - Hesse, Christiane; Siedler, Heike; Luntz, Steffen P.; Arendt, Bianca M.; Goerlich, Roland; Fricker, Ruth; Heer, Martina; Haefeli, Walter E. (Journal of applied physiology, 2005)
Prolonged microgravity alters the regulation of the peripheral vasculature. The influence of reduced food intake, as often observed in astronauts, on vascular function is unclear. In a randomized, four-phase, crossover study, the effect of simulated microgravity (13 days of bed rest), energetic restriction (−25%, fat reduced), and their combination on endothelium-dependent and -independent vasodilation was compared with ambulatory control conditions. Using venous occlusion plethysmography, cumulative intra-arterial dose-response curves to endothelium-dependent (acetylcholine) and -independent (sodium nitroprusside) vasodilators were constructed in 10 healthy male volunteers before and on day 13 of each of the four intervention periods. Bed rest combined with normoenergetic nutrition impaired the dose-response to acetylcholine (ANOVA, P = 0.004) but not to sodium nitroprusside, whereas hypoenergetic diet under ambulatory conditions improved responses to acetylcholine (P = 0.044) and sodium nitroprusside (P < 0.001). When bed rest was combined with hypoenergetic diet, acetylcholine responses did not change. Similarly, under control conditions, no change was observed. Individual changes in the total cholesterol-to-HDL ratio were correlated with changes in endothelial and vascular smooth muscle relaxation. In conclusion, short-term bed rest impairs endothelium-dependent arterial relaxation in humans. A hypoenergetic, low-fat diet modulates serum lipids, improves endothelium-dependent and -independent relaxation, and may antagonize the unfavorable effects of simulated microgravity on endothelial function.